Relationship Between Students’ Attitude Toward Mathematics and Academic Performance in Secondary School of Student - B.C., Gopal (Academic Journal of Mathematics Education, 2025)
The important role of attitude in learning Mathematics has attracted the attention of educational researchers and Mathematics teachers for a long time. As a result, literature is rich with empirical data regarding the connection between student attitudes and student achievement in Mathematics. The study employed a quantitative, descriptive-correlational design to examine the relationship between students’ attitudes toward mathematics and their academic performance. Data will be collected using a standardized attitude scale and academic records. Statistical analysis (Pearson correlation) will determine whether a significant relationship exists between the variables. The 100 students were selected through randomly, from 350 students of secondary level. Two sets of questionnaires were used to collect data from respondents after validation and reliability were confirmed. Students’ final exam scores served as an indicator of their academic accomplishments. The research revealed a notable connection between Relationship Between Students’ Attitude Toward Mathematics and Academic Performance in Secondary School of Student. It was recognized that teachers’ positive mindset inspired confidence in students, which subsequently led them to foster a positive attitude towards learning Mathematics. The study’s results were also in agreement with prior findings regarding the link between students’ attitudes and their performance in Mathematics. The findings’ implications are examined, and suggestions for practical application have been provided.